2020
DOI: 10.26803/ijlter.19.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Philosophy for Children (P4C) in Improving Critical Thinking in a Secondary Moral Education Class

Abstract: The purpose of this study was to identify the effect of Philosophy for Children (P4C) in improving critical thinking among students. The study was conducted via the quasi-experimental research comprising of 27 students placed in the experimental group while the remaining 34 students in the control group. The instrument used was the Ujian Kemahiran Menaakul (Test for Reasoning Skills) Centre for Teaching Thinking (UKMCTT). Based on the statistical t-test on critical thinking, the treatment group scored a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In line with the results of the present study, there are several experimental studies suggesting that CT teaching with the general approach (Al-Edwan, 2011 ; Alwehaibi, 2012 ; Arı, 2020 ; Arısoy & Aybek, 2021 ; Eldeleklioğlu & Özkılıç, 2008 ; Karadağ & Demirtaş, 2018 ; Lou, 2018 ; Marin & Halpern, 2011 ; Rahdar et al, 2018 ; Smith et al, 2018 ; Taghinezhad & Riasati, 2020 ), immersion approach (Bağ, 2020 ; Fung & Howe, 2012 ; Jensen Jr., 2015 ; Lopez et al, 2020 ; Marin & Halpern, 2011 ; Reed & Kromrey, 2001 ; Zulkifli & Hashim, 2020 ) and mixed approach (Ku et al, 2014 ; Plath et al, 1999 ; Welch et al, 2015 ) significantly improved CT skills. Also, after examining experimental studies of CT teaching, Tiruneh et al ( 2014 ) concluded that CT skills or dispositions were significantly improved in 80% of studies conducted with the general approach to CT teaching, 55% of studies conducted with the immersion approach to CT teaching and 67% of studies conducted with the mixed approach to CT teaching.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the results of the present study, there are several experimental studies suggesting that CT teaching with the general approach (Al-Edwan, 2011 ; Alwehaibi, 2012 ; Arı, 2020 ; Arısoy & Aybek, 2021 ; Eldeleklioğlu & Özkılıç, 2008 ; Karadağ & Demirtaş, 2018 ; Lou, 2018 ; Marin & Halpern, 2011 ; Rahdar et al, 2018 ; Smith et al, 2018 ; Taghinezhad & Riasati, 2020 ), immersion approach (Bağ, 2020 ; Fung & Howe, 2012 ; Jensen Jr., 2015 ; Lopez et al, 2020 ; Marin & Halpern, 2011 ; Reed & Kromrey, 2001 ; Zulkifli & Hashim, 2020 ) and mixed approach (Ku et al, 2014 ; Plath et al, 1999 ; Welch et al, 2015 ) significantly improved CT skills. Also, after examining experimental studies of CT teaching, Tiruneh et al ( 2014 ) concluded that CT skills or dispositions were significantly improved in 80% of studies conducted with the general approach to CT teaching, 55% of studies conducted with the immersion approach to CT teaching and 67% of studies conducted with the mixed approach to CT teaching.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…When Kurnaz (2017) compared the effect of general and immersion approaches on CT skills, the general approach was more effective than the immersion approach in enhancing CT skills ( η 2 = 0.23). Also, there have been many other experimental studies which concluded that the general approach (Arı, 2020 ; Eldeleklioğlu & Özkılıç, 2008 ; Karadağ & Demirtaş, 2018 ; Rahdar et al, 2018 ; Zulkifli & Hashim, 2020 ), the immersion approach (Bağ, 2020 ; Fung & Howe, 2012 ; Reed & Kromrey, 2001 ; Yuan et al, 2008 ) and the mixed approach (Ku et al, 2014 ; Plath et al, 1999 ) enhances CT. Although there have been several experimental studies of the effectiveness of these approaches, there is no consensus about which approach is more effective (Cáceres et al, 2020 ; Larsson, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hikmah (Wisdom) pedagogy is one of the teaching pedagogies which aims to encourage students to master 21st-century learning skills, such as cognitive skills (critical thinking, creative thinking), collaborative skills, communication skills, and noble values. Several studies on Hikmah (Wisdom) pedagogy focused on its influence in enhancing critical thinking (Hashim & Wan Yusoff, 2006;Othman & Hashim, 2007, Abdullah, 2009Hashim et al, 2017;Wan Yusoff, Hashim, Khalid, Hussein, & Kamaluddeen, 2018;Zulkifli & Hashim, 2020). Other studies highlighted qualitative research (Zulkifli & Hashim, 2020) while fewer studies concentrated on Hikmah pedagogy in questioning skills (Zulkifli & Hashim, 2019;Juperi, 2011;Alias, 2017).…”
Section: Revista De Ciencias Sociales Y Humanidadesmentioning
confidence: 99%
“…Several studies on Hikmah (Wisdom) pedagogy focused on its influence in enhancing critical thinking (Hashim & Wan Yusoff, 2006;Othman & Hashim, 2007, Abdullah, 2009Hashim et al, 2017;Wan Yusoff, Hashim, Khalid, Hussein, & Kamaluddeen, 2018;Zulkifli & Hashim, 2020). Other studies highlighted qualitative research (Zulkifli & Hashim, 2020) while fewer studies concentrated on Hikmah pedagogy in questioning skills (Zulkifli & Hashim, 2019;Juperi, 2011;Alias, 2017).…”
Section: Revista De Ciencias Sociales Y Humanidadesmentioning
confidence: 99%
“…Many studies have been undertaken on the effectiveness of P4C programs in improving thinking skills among students [ 2 , 5 , 6 , 7 ]. For instance, in Malaysia, applying P4C in the classroom could help students in improving critical thinking.…”
Section: Introductionmentioning
confidence: 99%